Laparoscopic vs. Open Surgical Repair of Subxiphoidal Hernia Following Median Sternotomy for Coronary Bypass - Analysis of the Herniamed Registry - Albrecht, Hendrik C.; Trawa, Mateusz; Köckerling, Ferdinand; Hukauf, Martin; Gretschel, Stephan (Frontiers in Surgery, 2020)
Introduction The repair of subxiphoidal incisional hernia following median sternotomy is technically demanding due to the specific anatomic situation and the lateral distracting forces in this region. Published data are available from retrospective reports with limited number of patients only. Materials and Methods This analysis of Herniamed registry data of patients with subxiphoidal incisional hernia following sternotomy for coronary bypass compared the perioperative and one year follow-up outcome of laparoscopic and open repair. Of 208 patients identified for the analysis 69 patients (33.2%) underwent laparoscopic and 139 (66.8%) patients had open repair. Results Concerning demographic data (gender, age, BMI, ASA score), risk factors and hernia size there were no significant differences between laparoscopic and open repair group. For intraoperative, postoperative and general complications as well as complication related re-operations no differences were seen between the groups. No advantage could be stated for laparoscopic repair regarding duration of operation and hospital stay. The recurrence rate at one year follow-up was higher in the laparoscopic group (7.2% vs. 2.2%; p=0.072). No differences were reported in the one year follow-up evaluation of pain at rest, pain on exertion and pain requiring treatment. Conclusion The repair of subxiphoidal incisional hernia is safe in both open and laparoscopic technique. With regard to the lower recurrence rate preference should be given to open repair.